A228 GASTROENTEROLOGISTS DIFFER IN THEIR PREFERRED MODE OF DELIVERY FOR PREGNANT WOMEN WITH ILEAL ANAL-POUCH ANASTOMOSIS. (1st March 2018) - Kuenzig, E; Mathivanan, M; Seow, C; Benchimol, E I; Panaccione, R; MacLean, A; Raman, M; Leung, Y
Abstract: Background: Ileal pouch-anal anastomosis (IPAA) is common among individuals with medically-refractory ulcerative colitis and familial adenomatous polyposis syndrome and is often performed during patients' reproductive years. Female infertility is common after IPAA but is decreased with laparoscopic procedures. Clinical practice guidelines recommend caesarean(C-) section but are based on little evidence. Aims: Determine recommendations given to pregnant women with IPAA by their gastroenterologist with regard to mode of delivery. Methods: Canadian gastroenterologists (GIs) were surveyed through the Canadian Association of Gastroenterology in May 2014. The questionnaire included demographic and clinical practice characteristics, and queried GIs on recommendations made to women with IPAA using a clinical vignette. We assessed physician characteristics associated with providing recommendations using a Fisher's exact test (categorical variables) and Wilcoxon rank-sum test (duration of clinical practice). Results: 57 gastroenterologists responded and had practiced for a median of 9 years (IQR 15). Two-thirds (38/56; 68%) of GIs practiced in an academic centre. Most GIs regularly (29/54; 54%) or sometimes (14/54; 20%) recommended a mode of delivery to women with IPAA of childbearing age. Physicians with ≥200 IBD patients in their practice and ≥10 patients with an IPAA were more likely to provide recommendations (p<0.05 for both; Table). Among gastroenterologists providing recommendations, 14/40 (35%) would recommend a trial of labour with a low threshold for C-section; 5/40 (13%), elective C-section; and 4/40 (10%), spontaneous vaginal delivery. The remaining physicians would defer to another specialty or patient preference. Conclusions: While the majority of gastroenterologists recommend a specific mode of delivery to their female patients of childbearing age with an IPAA, their recommendations are heterogeneous. This differs from the clinical practice guidelines on IBD in pregnancy, which recommend C-section in women with IPAA. Additional research is needed to identify the safest mode of delivery for these women and to assess uptake of these guidelines. Funding Agencies: CAG, CCC, CIHR